International tax planning under the destination-based cash flow tax - Auerbach, A; Devereux, M; Keen, M; Vella, J (National Tax Association, 2017)
This paper considers the implications of the destination-based cash flow tax (DBCFT) for three common ways of shifting taxable profits between countries: through manipulation of transfer prices, the use of debt, and locating intangible assets in low taxed jurisdictions. It shows that none of these planning devices would be available under a DBCFT, if adopted universally. This is because intra-group payments between two countries do not affect tax liabilities in either country . If adopted unilaterally, however, there would be an incentive to shift profit to the adopting country, at the expense of non-adopting countries.